Mengartikulasikan Relasi Musik dengan Radikalisme - Michael HB Raditya (Jurnal Studi Pemuda, 2016)
This article deals with relation between music and radicalism. In fact, religion and politics are more related with radicalism. In art perspective, visual art was more related with radicalism rather than music position—especially in Indonesia. In Indonesia music had minor relation with radicalism. According this fact, i would like to explore about music with radicalism with link with several songs, genres, and moda of production—especially relate with definition of radicalisme was rooted movement. The result that i got so far is songs, genres, and mode of production relate with counter-culture. Through counter-culture, radicalism movement that used by music can be running with a different portion, inter alia: change old system to new system, and deal with daily activity as a counter. This result made me more brightly to articulate that pathern and logic of radicalism not only about practical measured, but relate with ideology things.